A rare case of giant broad ligament leiomyoma mimicking abdominopelvic malignancy - Ganorkar, Ashlesha S.; Gupta, Brajesh B.; Chandak, Unmed; Dakhore, Sanjay; Sonewane, Chetan; Uikey, Rahul; Akulwar, Sanskruti; Nighot, Gaurav; Tatti, Ramesh (International Surgery Journal, 2025)
Broad ligament leiomyomas are uncommon extra-uterine fibroids which may pose as adnexal or retroperitoneal malignancies because of their position and presentation. A 44-year-old multiparous woman came with an incrementally worsening swelling in the abdomen for 1 year and pain in the abdomen for 15 days. On examination, there was a big abdominopelvic mass from the pelvis, firm in consistency, filling hypogastrium and going up to the upper abdomen. Contrast-enhanced computed tomography (CT) abdomen and pelvis revealed a large heterogeneously enhancing lobulated solid lesion (20×18×25 cm) in the abdominopelvic cavity, causing compression of nearby bowel, bladder, rectum, and ureters, with differential diagnoses including giant broad ligament leiomyoma, ovarian tumor, or desmoid tumor. Exploratory laparotomy with resection of the mass, total hysterectomy, and bilateral salpingo-oophorectomy was done. Histopathological examination established leiomyoma with hyalinization from the broad ligament. Broad ligament leiomyomas are less than 1% of all fibroids and tend to resemble adnexal tumors or sarcomas on imaging. They are hard to diagnose preoperatively, and imaging cannot always distinguish them from ovarian tumors. Surgical resection is still the treatment of choice. Broad ligament leiomyomas may be rare, but they must be included in the differential diagnosis of large abdominopelvic masses in women. Complete surgical resection is definitive treatment.